ASSESSMENT OF SAFE UTILIZATION OF HERBICIDES AWARENESS AMONG CROP FARMERS IN OWERRI WEST, NIGERIA - Ogbuji, Stanley I. (African Journal of Social and Behavioural Sciences, 2024)
The study examined the safe utilization of herbicides among crop farmers in Owerri-West Local Government Area of Imo State, their level of awareness on the dangers of herbicide misuse and compliance with safety measures in the use of herbicides. Data were collected with a structured questionnaire administered to eighty crops farmers The data collected were analysed using descriptive statistical techniques. The Likert scale was used in analysing the level of awareness while chi-square was employed for the research hypothesis. The findings of the study showed that farmers have a high level of awareness in the use herbicides by crop farmers in the study area. The study also revealed that the most perceived problems in the use of herbicides by crop farmers in the study area are inadequate equipment (x= 3.19) and skill (x= 2.84) respectively and spraying of herbicides to unintended plants (x= 2.55), while the level of precautionary measure on eating, drinking and talking while spraying is high (x = 3.21). The research hypothesis showed no significant relationship between farmers’ level of awareness and the safe utilization of herbicides in the study area. Generally, herbicide application among crop farmers in the study area is not safe for health and the environment, hence the study recommends among others, the training and retraining of farmers on the safe utilization of herbicides in crop production so as to inculcate the necessary skills in the use of herbicides by the government using agricultural extension workers and also with the collaboration of the chemical companies and non-governmental organizations and farmers’ association where available.